2014
DOI: 10.1002/ab.21553
|View full text |Cite
|
Sign up to set email alerts
|

Face the consequences: Learning about victim's suffering reduces sexual harassment myth acceptance and men's likelihood to sexually harass

Abstract: Prior research has shown that (1) better knowledge about the consequences of rape goes along with less rape-supportive attitudes and lower rape proclivity, and (2) empathy with the victims correlates negatively with sexual aggression. In two experiments, the authors combined these approaches in order to reduce sexual harassment myth acceptance (SHMA) and the likelihood to sexually harass (LSH). In Study 1, 101 male and female university students read a report describing sexual harassment as either serious or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 119 publications
3
63
0
2
Order By: Relevance
“…Diehl and colleagues [92], for instance, referred to Hofstede’s cultural dimensions theory [93] and the global gender gap index [94] in order to relate their results to other cultural settings. These authors conclude that one may provisionally declare that Germany does not differ very much from other European Countries or the USA with respect to gender-related attitudes and societal development.…”
Section: Discussionmentioning
confidence: 99%
“…Diehl and colleagues [92], for instance, referred to Hofstede’s cultural dimensions theory [93] and the global gender gap index [94] in order to relate their results to other cultural settings. These authors conclude that one may provisionally declare that Germany does not differ very much from other European Countries or the USA with respect to gender-related attitudes and societal development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has established excellent reliability and validity of the ISHMA scale. For example, the ISHMA is negatively correlated with trait empathy (Diehl et al, 2014) and is positively correlated with sexism and hostility toward women (Lonsway et al, 2008). The ISHMA is also a positive predictor of gender harassment and unwanted sexual attention over the Internet (Diehl et al, 2012).…”
Section: Methodsmentioning
confidence: 95%
“…Lonsway et al (2008), for example, reported a negative correlation between previous Moral Disengagement in Sexual Harassment 33 participation in sexual harassment awareness training and overall endorsement of SHMA. More recently, experimental research found that exposure to the negative consequences of sexual harassment attenuated SHMA among men and women, and even lowered men's self-reported proclivity to harass (Diehl et al, 2014). Given the conceptual proximity of moral disengagement and SHMA in terms of their function, it is expected that participation in training will exert similar positive effects in reducing moral disengagement and its adverse influence on harassment judgments and perpetration of harassing behavior.…”
Section: Practical Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the most pivotal findings to emerge was the existence of gender differences in expressing empathy, since women seem to express more empathy towards rape victims (Anastasio & Costa, 2004;Diehl et al, 2014;George & Martínez, 2002;Mellor, Fung, & Mammat, 2012;Miller, Amacker, & King, 2011;Osman, 2011Osman, , 2014Paul et al, 2014;Sakallı-Uğurlu et al, 2007;Smith & Frieze, 2003) and men towards perpetrators (Ferrão et al, 2013;Mellor et al, 2012;Osman, 2011;Sakallı-Uğurlu et al, 2007;Smith & Frieze, 2003). Rape victim empathy has also been shown to be negatively related to rape myth acceptance (Forbes, Adams-Curtis, Pakalka, & White, 2006;Gerger et al, 2007;Jimenez & Abreu, 2003;Mason et al, 2004;Miller et al, 2011).…”
Section: Rape Empathymentioning
confidence: 99%